Respuesta :
Answer:
x=4
Step-by-step explanation:
Simplifying
-1(7 + -4x) = 9
(7 * -1 + -4x * -1) = 9
(-7 + 4x) = 9
Solving
-7 + 4x = 9
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '7' to each side of the equation.
-7 + 7 + 4x = 9 + 7
Combine like terms: -7 + 7 = 0
0 + 4x = 9 + 7
4x = 9 + 7
Combine like terms: 9 + 7 = 16
4x = 16
Divide each side by '4'.
x = 4
Answer:
x = 4
Step-by-step explanation:
-(7 - 4x) = 9 (Given)
-7 + 4x = 9 (Distributed)
-7 + 4x + 7 = 9 + 7 (Add 7 on both sides)
4x = 16 (Simplify)
4x/4 = 16/4 (Divide 4 on both sides)
x = 4 (Simplify)